Water-based graphene quantum dots dispersion as a high-performance long-term stable nanofluid for two-phased closed thermosyphons - Soleymaniha, Mohammadreza; Amiri, Ahmad; Shanbedi, Mehdi; Chew, Bee Teng; Wongwises, Somchai (Elsevier, 2018)
Water-based graphene quantum dots (GQD) suspension has great potential for different heat transfer applications as a novel coolant due to their unique colloidal stability, high thermal conductivity and low penalty for rheological properties once loading GQD. To this end, graphene quantum dots were firstly prepared through a new and cost-effective exfoliation procedure. Based on the morphological characterization, the average thickness and diameter of the synthesized amine treated-GQD (AGQD) were determined as mostly less than 1 nm and in the range of 5–20 nm, respectively. Case studies show that water-based AGQD nanofluid at very low weight fractions shows a considerably higher thermal conductivity than that of base fluid. In a detailed rheological investigation of the water-based AGQD nanofluid, no noteworthy increase was observed in comparison with the base fluid, which is considered as a major benefit for this novel generation of coolants. The water-based AGQD nanofluids were also found to be especially more effective in the thermosyphon in terms of overall thermal properties such as net heat transfer, and thermal efficiency, and rheological property such as effective viscosity, as well as, total pressure drop in comparison to the distilled water. Since the water-based AGQD nanofluids show no sedimentation, high thermal conductivity and fairly no effect on rheological properties, it would provide an economical approach for enhancing the performance of industrial heat pipes and thermosyphons.